PRAGMATIC PROBLEMS OF TRANSLATION AND THEIR SOLUTIONS - Gafurova Nozimaxon Ikramovna; Meliboyeva Nazokatxon Elyor kizi (TADQIQOTLAR.UZ, 2023)
Abstract:Translation is an intricate process that involves transferring meaning from one language to another while considering various cultural, linguistic, and pragmatic factors. However, translators often encounter pragmatic obstacles that affect the accuracy and effectiveness of their translations. This article examines common pragmatic problems in translation and presents potential solutions. By understanding and addressing these challenges, translators can enhance the quality and communicative effectiveness of their work, ensuring successful cross-cultural communication.